A framework in ubiquitous computing environment for providing intelligent responses - Mantoro, Teddy; Johnson, Chris William; Ayu, Media Anugerah (2009)
This paper focuses on a new framework for an Intelligent Environment to respond intelligently to persons being in a ubiquitous computing environment. The framework contains 1. context notations to have a three-key-predicate relations (location, activity and response awareness), 2. taxonomy of the context aware computing in responding to user activity and 3. context aware application design to respond intelligently based on the sensor management and context representation. The framework can be used as a basis development of large-scale optimizations for the handling growth of sensor data and for providing intelligent response in the intelligent computing environment. The paper also provides a proof of concept of how environment response can be delivered to the user.